Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K.; Barnum, Mary
"Four major goals were established for this the seventh edition of the Foundations of Athletic Training. The primary goal was to support the transition of the athletic training education program from the undergraduate to the graduate level degree by including content identified in Section IV (Curricular Content) of the CAATE® 2020 Standards for Accreditation of Professional Athletic Training Program. Specific content relating to core competencies, patient/client care, prevention, health promotion, and wellness and health care administration are introduced early and imbedded throughout the text. A second goal was to continue to provide the most current and comprehensive evidence-based content related to the prevention, assessment, and management of injuries and illnesses sustained by physically active individuals. We have adopted a writing style that promotes clinical reasoning, seeks to demonstrate the value of utilizing differential diagnosis strategies, and moves the learner toward adopting reflective practice skills. In an effort to continue our tradition of providing special pedagogical features in a visually pleasing format, multicolor borders and formatting have been used to identify critical boxes, application strategies, and tables as a way to highlight key information"--Provided by publisher.